2015
DOI: 10.7554/elife.10841
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic integration of Netrin and ephrin axon guidance signals by spinal motor neurons

Abstract: During neural circuit assembly, axonal growth cones are exposed to multiple guidance signals at trajectory choice points. While axonal responses to individual guidance cues have been extensively studied, less is known about responses to combination of signals and underlying molecular mechanisms. Here, we studied the convergence of signals directing trajectory selection of spinal motor axons entering the limb. We first demonstrate that Netrin-1 attracts and repels distinct motor axon populations, according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
98
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 77 publications
(128 reference statements)
10
98
1
Order By: Relevance
“…However while there are trace amounts of netrin1 expression in the netrin1 lacZ/lacZ FP (chevrons, Fig. 2B, H, L) there is no detectable netrin1 transcript in the netrin1 lacZ/lacZ VZ at any stage or any detectable netrin1 protein (Poliak et al, 2015; Varadarajan et al, 2017). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…However while there are trace amounts of netrin1 expression in the netrin1 lacZ/lacZ FP (chevrons, Fig. 2B, H, L) there is no detectable netrin1 transcript in the netrin1 lacZ/lacZ VZ at any stage or any detectable netrin1 protein (Poliak et al, 2015; Varadarajan et al, 2017). …”
Section: Resultsmentioning
confidence: 97%
“…The wall provides a substrate for growth, but is not itself penetrated by the ivy. It remains unresolved how widely hederal boundaries act to establish neural circuits, however further putative examples have been observed in both the central and peripheral nervous systems (Burrill and Easter, 1994; Poliak et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EphB2 modulates radial migration, proliferation and cell fate of neural progenitor cell in the subventricular zone (Chumley et al, 2007; Katakowski et al, 2005). Interestingly, Netrin-1 and EphB2 have been shown to work synergistically through the Src family kinase-signaling pathway during neural circuit assembly (Poliak et al, 2015). However, further mechanistic studies will be required to validate the significance and underlying molecular mechanisms by which these putative genes potentially cause viral-mediated microcephaly.…”
Section: Discussionmentioning
confidence: 99%
“…10E), implicating that another mechanism can act as a backup system if both Slit and Netrin cues are missing. In fact, spinal motor axon navigation is also dependent on other floor plate-derived signals, such as Sema3A and Ephrins (Bai et al, 2011; Poliak et al, 2015), suggesting that the precise motor exit points could be determined by multiple guidance signals. Furthermore, we observed that spinal motor axons still exited out the spinal cord in our Slit/Robo or Netrin-1/DCC mutants.…”
Section: Discussionmentioning
confidence: 99%